Our future ballot - Avery, Herman Willard (My University, 1891)
Introduction: For years under oppression, held responsible to laws on whose making they had no voice, compelled to give support to institutions which violated conscience, prevented from doing what in their own minds they believed to be right; no people had a more sensitive sacred regard for liberty than our fore fathers who landed on the historic sail of Massachusetts. The consecrated devotion that went up from those reverential sails challenges our admiration. I fancy I see more in it than religious freedom. I cannot but think when that fervent puritanic prayer went up to Heaven, the angel of liberty descended to earth and declared all men equal, in rights and privileges –sovereigns of themselves.
Citation: Avery, Herman Willard. Our future ballot. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Politics; Voting; Ballots; America; Theses; Manuscripts (documents)